1, 3-Dimethyl-2-phenyl-1, 3-diazaphospholidine-2-oxide as ligand for the preparation of luminescent lanthanide complexes. Issue 9 (3rd May 2019) - Bortoluzzi, Marco; Gobbo, Alberto
Abstract: Europium(III) coordination compounds having general formula [Eu(β-dike)3 L2 ] (β-dike = dibenzoylmethanate, tenoyltrifluoroacetonate; L = 1, 3-dimethyl-2-phenyl-1, 3-diazaphospholidine-2-oxide) were isolated and characterized. The complexes exhibited bright red emission associated to the 5 D0 → 7 FJ transitions of the metal center upon excitation with near-UV light, with intrinsic quantum yields around 51% and 65%, respectively, for the dibenzoylmethanate and tenoyltrifluoroacetonate derivatives. More information about the behavior of 1, 3-dimethyl-2-phenyl-1, 3-diazaphospholidine-2-oxide as an antenna-ligand towards trivalent lanthanide ions was obtained by its coordination to [Ln(NO3 )3 ] (Ln = Eu, Gd, Tb) metal fragments. Graphical Abstract: